Emerging immune therapies in type 1 diabetes and pancreatic islet transplantation - Schneider, D. A.; Kretowicz, A. M.; von Herrath, M. G. (Diabetes, obesity & metabolism, 2013)
In type 1 diabetes (T1D) the immune system attacks insulin‐producing pancreatic β‐cells. Unfortunately, our ability to curb this pathogenic autoimmune response in a disease‐ and organ‐specific manner is still very limited due to the inchoate understanding of the exact nature and the kinetics of the immunological pathomechanisms that lead to T1D. None of the clinical immune interventions thus far, which focused primarily on new‐onset disease, were successful in producing lasting remission or curbing recurrent autoimmunity. However, these studies do provide us access to a tremendous amount of clinical data and specimens, which will aid us in revising our therapeutical approaches and defining the highly needed paradigm shift in T1D immunotherapy. Analysing the foundation and the results of the most current T1D immunotherapeutic trials, this article gives an outlook for future directions of the field.